Careers in dairy: adolescents perceptions and attitudes. Issue 5 (20th October 2019) - Beecher, Marion; Gorman, Monica; Kelly, Paidi; Horan, Brendan
ABSTRACT: Purpose: This paper examines the attitudes and perceptions of Irish adolescents towards potential careers in dairy farming within the context of generational renewal for a dynamic agri-food sector. Design/methodology/approach: The lens of occupational choice theory was used to present a framework within which potential careers are considered. A questionnaire-survey was undertaken with 490 Irish adolescents (15–18 yrs). Findings: While parents have the greatest influence on the career choices of adolescents, there was a positive correlation between studying agricultural science in school and considering an agricultural related career. Adolescent's attitudes towards careers in dairy farming were subject to perceptions about gender, farm ownership, potential income and work-life balance. There was a high degree of openness to gaining work experience on dairy farms. Practical implications: With an increased interest in agricultural science in second level schools in Ireland, the findings point to opportunities to influence awareness and attitudes of adolescents and their parents about career possibilities in dairy farming and to encourage both familial and non-familiar generational renewal. Theoretical implications: The paper contributes an understanding of career choices and aspirations in adolescence to add to the growing body of literature on generational renewal in farming. Originality/value: This paper focuses specifically on dairy farming, providing more detailed information about adolescents' perceptions of dairy farming careers. The study highlights the positive relationship between studying agricultural science in school and subsequent interest in agricultural related careers. The results indicate that generation renewal in agriculture can be enhanced by giving increased attention to agriculture in school curricula.